Eksperimen Terbimbing untuk Mengubah Pemahaman Mahasiswa tentang Beda Potensial dan Arus dalam Rangkaian Arus Searah - Niluh Eka Puspayanti; I Komang Werdhiana (Jurnal Kreatif Online, 2021)
This study aimed to describe a guided experiment to change students' understanding of voltage and current in a direct current circuit. The study was qualitative research. The subjects were physics education students. The experiment was followed by 16 students. Data collection techniques were test and interview. The results of the pretest showed that many students had misconceptions about the concept of voltage and current in a direct current circuit. After conducting the experiment, the students answered the given test again. The test results show that the experiment carried out could improve students' understanding of the concept of direct current electric circuits. So, it can be concluded that guided experiments can change students' understanding of voltage and current in direct current circuits.